LOW-TEMPERATURE HYDROTHERMAL ALTERATION OF SILICIC GLASS AT THE PACMANUS HYDROTHERMAL VENT FIELD, MANUS BASIN: AN XRD, SEM AND AEM-TEM STUDY - Glorgetti G.; Monecke T.; Kleeberg R.; Hannington M.D. (My University, 2006)
Dacitic lava recovered from the immediate subsurface of the submarine PACMANUS hydrothermal vent field exhibits variable degrees of hydrothermal alteration resulting from the interaction of the glassy volcanic rocks with mineralizing hydrothermal fluids at relatively low temperatures. Transmission electron microscopic (TEM) investigations revealed that the felsic volcanic glass transformed to nm-thick smectitic flakes of the montmorillonite-beidellite series via a dissolution and reprecipitation mechanism. The process of smectite formation did not proceed through X-ray amorphous or poorly crystalline transitional phases. Alteration of the glass was found to be most pronounced adjacent to perlitic cracks and vesicles that form an interconnected network focusing fluid flow. Glass dissolution adjacent to these fluid pathways resulted in a characteristic alteration texture at the nm scale; the intensely altered groundmass contains round cavities that are partially coated or filled by smectitic flakes. The Mg content of the smectite broadly increases towards the fluid pathways. Smectitic flakes with compositions corresponding to saponite occur in the intensely altered groundmass adjacent to perlitic cracks. In addition, anatase, apatite and rare kaolinite were formed during the alteration of the volcanic glass. Primary minerals including plagioclase show only minor textural evidence of alteration. However, some primary plagioclase laths show X-ray amorphous rims depleted in Na, Ca and Al. The TEM investigations of the dacitic lava samples from the PACMANUS vent field demonstrate that volcanic glass has a higher susceptibility to hydrothermal alteration at low temperatures than most associated primary phases. The findings of the study suggest that the interaction between the volcanic rock and the hydrothermal fluids proceeded under open-system conditions leading to a mobilization of alkali elements and a redistribution of Ti at the nm scale. The Mg required for the formation of trioctahedral smectite was supplied by the hydrothermal fluids.
Keywords: GLASS-SMECTITE CONVERSION; HYDROTHERMAL ALTERATION; PACMANUS VENT FIELD; TRANSMISSION ELECTRON MICROSCOPY